Curdione Ameliorated Doxorubicin-Induced Cardiotoxicity Through Suppressing Oxidative Stress and Activating Nrf2/HO-1 Pathway. Issue 2 (August 2019) - Wu, Zimei; Zai, Wenjing; Chen, Wei; Han, Yuxuan; Jin, Xin; Liu, Hongrui
Abstract : Abstract: Doxorubicin (DOX) is a representative antibiotic of terpenoids and clinically used in the treatment of various malignant tumors. However, its application is limited by the cardiotoxocity. Curdione, an extract from Rhizoma Curcumae, has many promising pharmacological effects including protecting acute liver injury and cerebral ischemia. It is still unknown whether curdione has a protective function for DOX-induced cardiotoxicity. In our study, we investigated the protective effects of curdione against DOX-induced cardiotoxicity. Our results showed that curdione attenuated DOX-induced growth inhibition and release of lactic dehydrogenase in a concentration-dependent manner. And curdione ameliorated the histopathological damage, reduced the elevation of serum creatine kinase-MB isoenzyme (CK-MB) and lactic dehydrogenase by DOX. Furthermore, curdione inhibited DOX-induced cell apoptosis and modulated the expression of Bcl-2 and Bax proteins, as well as abrogated DOX-induced reactive oxygen species accumulation and prevented mitochondria dysfunction. Further study indicated that curdione decreased DOX-induced phosphorylation of extracellular signal-regulated kinase1/2 (Erk1/2) and c-Jun-N-terminal kinase and activated nuclear factor-erythroid 2–related factor 2/heme oxygenase 1 (Nrf2/HO-1) signal pathway. Our results suggested that curdione maybe is a new and feasible strategy to prevent DOX-induced cardiotoxicity through monitoring multiple targets.